Not all stressors are equal: behavioral and endocrine evidence for development of contextual fear conditioning after a single session of footshocks but not of immobilization - Daviu, Núria; Delgado-Morales, Raul; Nadal, Roser; Armario, Antonio (Frontiers in Behavioral Neuroscience, 2012)
Exposure of animals to footshocks (FS) in absence of any specific cue results in the development of fear to the compartment where shocks were given (contextual fear conditioning), and this is usually evaluated by time spent freezing. However, the extent to which contextual fear conditioning always develops when animals are exposed to other stressors is not known. In the present work we firstly demonstrated, using freezing, that exposure of adult rats to a single session of FS resulted in short-term and long-term contextual fear conditioning (freezing) that was paralleled by increased hypothalamic-pituitary-adrenal (HPA) activation. In contrast, using a similar design, no HPA or behavioural evidence for such conditioning was found after exposure to immobilization on boards (IMO), despite this stressor being of similar severity as FS on the basis of standard physiological measures of stress, including HPA activation. In a final experiment we directly compared the exposure to the two stressors in the same type of context and tested for the development of conditioning to the context and to a specific cue for IMO (the board). We observed the expected high levels of freezing and the conditioned HPA activation after FS, but not after IMO, regardless of the presence of the board during testing. Therefore, it can be concluded that development of fear conditioning to context or particular cues, as evaluated by either behavioural or endocrine measures, appears to be dependent on the nature of the aversive stimuli, likely to be related to biologically preparedness to establish specific associations.